Parental control in alcohol consuming and non-consuming parents from the perspective of their adolescent daughters - Bustamante Correa, Rosa Fabiola (2015)
In order to determine if there are significant differences between parental control of parents who are consumers and non-consumers of alcohol, from the perception of their daughters, were studied 643 adolescent girls of 15-17 years of age who are in highschool from seven educational institutions in four districts of Lima. For purposes of the study were administered The Parental Psychological Control Scales (Barber, 1996), and The Children of Alcoholics Screening Test (CAST 6) (Jones, 1983). We found significant differences in parental control between the two groups. More precisely, there were evidence that the adolescents perceive greater parental control from parents who they categorized as alcohol consumers.